Territorial Differences in the Italian 'Social Model'. Issue 1 (2nd January 2016) - Colombo, Sabrina; Regini, Marino
Abstract : Colombo S. and Regini M. Territorial differences in the Italian 'social model', Regional Studies . As elsewhere in Europe in the post-Second World War period the Italian political élites shared the belief that market economies should not be left entirely to the market, but rather follow some sort of 'social model'. However, while Italy did join Continental European countries in developing such an institutional arrangement, this was differently shaped in the different territorial areas of the country. This paper briefly sketches what is commonly regarded as the typical configuration of this social model and then describes how each of its features works differently in the different territorial contexts, finding a deep dividing line between the Centre–North and the South.